2018 Global Food Policy Report (English) - Fan, Shenggen (2018)
Shenggen Fan Canadian perspectives on the 2018 Global Food Policy Report Ottawa, ON, Canada Co-Organized by International Development Research Centre (IDRC) and International Food Policy Research Institute (IFPRI) with the collaboration of Global Affairs Canada May 01, 2018 - 09:00 to 10:30 am EDT Delta Hotels Ottawa City Centre, Ottawa, ON